Application of digital holographic microscopy and microfluidic chips to the measurement of particle size distribution of fly ash after a wet electrostatic precipitator. (April 2018) - Zhou, Hao; Yang, Zheng; Yao, Zhenguo; Cen, Kefa
Abstract: In-line digital holographic microscopy is used to obtain a particle size distribution of fly ash after wet electrostatic precipitators. A polydimethylsiloxane microfluidic chip with a cross section of 50 × 200 µm 2 is fabricated to offer a suitable experimental environment and constant background. Equivalent Charge Coupled Device pixels are calibrated to be 0.1016 µm, leading a 35.4-times magnification. A sample containing standard particles of 2 µm is first analyzed to confirm the validity and stability of the digital holographic microscopy under flowing condition. The average diameter is reconstructed to be 2.03 µm, leading to a relative standard deviation of 1.5%. Then samples acquired after the wet electrostatic precipitator of a coal power plant is analyzed. Large amounts of holographic pictures are taken and reconstructed to obtain a particle size distribution from 0.5 µm to 3.52 µm. Finally the obtained results are compared with that from a laser particle size analyzer. The acceptable deviation indicates that the method is feasible and accurate to measure fly ash after wet electrostatic precipitators as well as other microparticles. Highlights: A holographic system based on microfluidic chips is proposed to measure the fly ash. Result of size standard particles confirms the method under flowing condition. Particle size distribution form the proposed method is compared with that from a laser particle size analyzer.